Numerical analysis of a vehicle wake with tapered rear extensions under yaw conditions. Issue 179 (August 2018) - Urquhart, Magnus; Sebben, Simone; Sterken, Lennert
Abstract: In recent years, governmental legislation and consumer demands are driving the development of more energy efficient road vehicles. One of the aspects considered when increasing efficiency is the aerodynamic performance of the vehicle. The focus of this paper is on wake effects for a vehicle with tapered rear extensions in side wind conditions. For this purpose, numerical simulations are analysed using post-processing techniques such as Proper Orthogonal Decomposition (POD) and Two-point correlation. The extensions protrude 150 mm from the perimeter of the base and are investigated in two configurations: with a smooth taper and with an added kick. The kick realigns the perimeter base flow to the vehicle's driving direction. As the oncoming flow angularity is increased, drag increases for the investigated angles. The smooth extensions provide the greatest drag improvement at 0° yaw while the extensions with a kick yield additional benefits at yaw, effectively reducing the vehicles drag sensitivity to side wind. A large scale twisting motion is present at yaw for the baseline and smooth extensions configurations which is reduced when adding a kick to the extension. Highlights: Low drag cases were found to have recirculating flow aligned with driving direction. Tapered extensions with a flow aligning kick reduce drag increase from sidewind. The extensions with a kick reduce a large scale twisting structure in the wake. Strong anti-symmetric modes could not alone be linked to high drag. Base pressure fluctuations reduced with extensions, especially at impingement location.